2002
DOI: 10.1007/s11663-002-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the direct synthesis of molycarbide by reduction-carburization of molybdenite in the presence of lime

Abstract: Kinetic studies were conducted on the carbon monoxide reduction of molybdenite in the presence of lime. Contrary to the expectation that the MoS 2 (s) ϩ CaO (s) ϩ CO (g) reaction will result in metal formation, molycarbide was found to form and no Mo was detected in the product. This is explained on the basis of thermochemical considerations, which indicate that the Mo 2 C formation is more feasible by eight orders of magnitude. The effects of quantity of lime in the charge, CO flow rate, temperature (1123 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Thus C 2 H 4 is the primary reactant that decomposes to form active carbon species to dissociate Mo-S bonds at elevated temperature. The resulted Mo is supposed to act as a catalyst for graphene growth from the initial nuclei while it also reacts with the active carbon species to form the carbide owing to the strong affinity between Mo and C. [20,21] The similar observations on the carbide formation have been reported during graphene or carbon nanotube growth on transition metal catalysts, [22,23] but it is the first time to straight forwardly observe this phenomenon with the substrate of atomic layered material of MoS 2 . To get a better picture of possible reactions, we calculated the Gibbs free energy of possible reactions as shown in Figure 3.…”
mentioning
confidence: 53%
“…Thus C 2 H 4 is the primary reactant that decomposes to form active carbon species to dissociate Mo-S bonds at elevated temperature. The resulted Mo is supposed to act as a catalyst for graphene growth from the initial nuclei while it also reacts with the active carbon species to form the carbide owing to the strong affinity between Mo and C. [20,21] The similar observations on the carbide formation have been reported during graphene or carbon nanotube growth on transition metal catalysts, [22,23] but it is the first time to straight forwardly observe this phenomenon with the substrate of atomic layered material of MoS 2 . To get a better picture of possible reactions, we calculated the Gibbs free energy of possible reactions as shown in Figure 3.…”
mentioning
confidence: 53%
“…Many researchers have investigated the thermodynamics and kinetics of molybdenite processing by such an environmental friendly approach, using different reducing agents, i.e., hydrogen, 2,3 carbon, 4 and carbon monoxide. 5 The reduction path and mechanism have been considered as well. According to Prasad et al, 5 Mo 2 C appears to be formed from carbon monoxide reduction of MoS 2 + CaO by a threesuccessive solidÀgas reaction path.…”
Section: Introductionmentioning
confidence: 99%
“…5 The reduction path and mechanism have been considered as well. According to Prasad et al, 5 Mo 2 C appears to be formed from carbon monoxide reduction of MoS 2 + CaO by a threesuccessive solidÀgas reaction path.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that molybdenite leaches slowly in dilute (1-4 M) nitric acid at room temperature [3] and the leaching of MoS 2 by sulfuric acid is a very slow process [4]. Beyond these studies, other pyrometallurgical processes such as chlorination [5], salt roasting [6], lime roasting [7] and carbothermal reduction of molybdenite in the presence of lime [8] were investigated. Presently, increasing the dissolution rate of molybdenite is a key problem for this mineral.…”
Section: Introductionmentioning
confidence: 99%